Association of Thyroid Dysfunction with Young Diabetic Subjects in a Bangladeshi Population - Rashid, DA; Rashid, MA; Hannan, JMA; Faruque, M; Nahar, Q; Ali, L (Bangladesh Medical Journal, 2009)
The study was a prospective study carried out in the Research Division of Bangladesh Institute of Research and Rehabilitation in Diabetes, Endocrine and Metabolic Disorders (BIRDEM), Dhaka. The present study was designed to investigate the thyroid dysfunction specially total and free levels of serum T3 and T4, and TSH in young diabetic subjects. A total number of 49 diabetic subjects and 28 controls were recruited in this study. Plasma glucose was measured by glucose oxidase method, HbA1C by modified HPLC method, serum total T3, total T4, free T3, free T4, TSH and C-peptide were measured by fluorescence-based ELISA technique. Age and BMI of the controls, Type 2 diabetic and FCPD subjects were matched. Total T3 concentration in FCPD and type 2 groups were significantly lower than the control group (p<0.001). T3 in FCPD was lower than that of type 2 (p<0.01). No significant difference was shown in T4 concentrations among the three groups of study subjects but there was significant lower in T3/ T4 ratio in FCPD and type 2 than control groups (p<0.001, p<0.01 respectively). The concentration of Free T3 was lower in FCPD group (p<0.01) than controls and type 2 DM. Free T4 and TSH concentration were similar in all the groups. With increasing of fasting serum glucose and HbA1C in the subjects, serum T3, Free T3, and T3/ T4 ratio were decreased significantly. Irrespective of groups, fasting serum glucose and HbA1C showed negative correlation with serum T3 (FSG: r= -0.591, p= 0.001; HbA1C: r= -0.68, p= 0.001) and Free T3 (FSG: r= -0.421, p= 0.001; HbA1C: r= -0.381, p= 0.001). C-peptide showed positive correlation with T3 and Free T3 (T3: r= 0.429, p= 0.001; Free T3: r= 0.228, p= 0.05). The existance of low T3 syndrome is confirmed in young Bangladeshi diabetic population regarding free levels of T3 and T4. The values of the free hormones (low FT3 and normal FT4) as well as normal TSH explain clinically euthyroid state of the subjects. The data also demonstrated that the lowering of T3 in diabetic subjects seems to be related with their degree of hyperglycemia. Key Words: Thyroid Dysfunction, Young Diabetes Mellitus. DOI: 10.3329/bmj.v36i2.3608 Bangladesh Medical Journal 36(2) 2007 34-38